2012
DOI: 10.1259/bjr/28575455
|View full text |Cite
|
Sign up to set email alerts
|

Missed rib fractures on evaluation of initial chest CT for trauma patients: pattern analysis and diagnostic value of coronal multiplanar reconstruction images with multidetector row CT

Abstract: Objective: The objective of this study was to review the prevalence and radiological features of rib fractures missed on initial chest CT evaluation, and to examine the diagnostic value of additional coronal images in a large series of trauma patients. Methods: 130 patients who presented to an emergency room for blunt chest trauma underwent multidetector row CT of the thorax within the first hour during their stay, and had follow-up CT or bone scans as diagnostic gold standards. Images were evaluated on two se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 24 publications
(33 reference statements)
2
65
0
Order By: Relevance
“…It has already been shown that the use of MPR or volume rendered (VR) images in comparison to transverse CT images may improve the detection rate [11,12]. We used CT images with 1 mm slice thickness allowing for three-dimensional reformation and compared these to the unfolded rib images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been shown that the use of MPR or volume rendered (VR) images in comparison to transverse CT images may improve the detection rate [11,12]. We used CT images with 1 mm slice thickness allowing for three-dimensional reformation and compared these to the unfolded rib images.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture location was subdivided into an anterior, lateral and posterior part, as previously described by Cho et al [11] and Livingston et al [14]. Accordingly, missed fractures were sub-classified in terms of localization (anterior, lateral, posterior) and fracture characteristics (normal/dislocated/buckled/incomplete).…”
Section: Image Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumomediastinum was differentiated from pneumothorax by the presence of the internal septa. [1115] Hemothorax, hemopericardium, hemoperitoneum were defined as “blood density (30–100 HU) within the pleural cavity, pericardium and abdominal cavity,” respectively. Mediastinal hematoma was defined as “inhomogeneous soft tissue density within the mediastinal fat, with obscuration or obliteration.” Chest wall hematoma was defined as “area of soft tissue density causing anatomical alteration.” We are aware of the critical limitation for assessment of aortic injury and upper abdominal injury using non-contrast CT, so LDCT without contrast enhancement of this current study was not appropriate for proper evaluation of aortic injury and upper abdominal injury.…”
Section: Methodsmentioning
confidence: 99%
“…A nondisplaced rib fracture is defined as a rib fracture with complete cortical disruption but with maintained alignment, usually involving the medullar bone and both the inner and outer cortices ( Figure 1); it is seen such a lucent line on radiographs or CT images (14). Stress rib fractures are overuse injuries that occur when there is an abnormal force on normal underlying bone.…”
Section: Types Of Rib Injuriesmentioning
confidence: 99%